Antimicrobial, antioxidant and cytotoxic activities of the leaf and stem extracts of Carissa bispinosa used for dental health care - Wanda Shekwa; Tsolanku Sidney Maliehe; Peter Masoko (BMC, 2023)
Abstract Background Carissa bispinosa (L.) Desf. ex Brenan is one of the plants used traditionally to treat oral infections. However, there is limited data validating its therapeutic properties and photochemistry. The aim of this study was to investigate the protective efficacy of the leaf and stem extracts of C. bispinosa against oral infections. Methods The phenolic and tannin contents were measured using Folin-Ciocalteau method after extracting with different solvents. The minimum inhibitory concentrations (MIC) of the extracts were assessed using the microdilution method against fungal (Candida albicans and Candida glabrata) and bacterial (Streptococcus pyogenes, Staphylococcus aureus and Enterococcus faecalis) strains. The 2-diphenyl-1-picrylhydrazyl (DPPH) and ferric reducing power (FRP) models were utilised to assess the antioxidant potential of the extracts. Cytotoxicity of the leaf acetone extract was evaluated using the methylthiazol tetrazolium assay. Results The methanol leaf extract had the highest phenolic content (113.20 mg TAE/g), whereas hexane extract displayed the highest tannin composition of 22.98 mg GAE/g. The acetone stem extract had the highest phenolic content (338 mg TAE/g) and the stem extract yielded the highest total tannin content (49.87 mg GAE/g). The methanol leaf extract demonstrated the lowest MIC value (0.31 mg/mL), whereas the stem ethanol extract had the least MIC value of 0.31 mg/mL. The stem methanol extract had the best DPPH free radical scavenging activity (IC50, 72 µg/mL) whereas the stem ethanol extract displayed maximum FRP with absorbance of 1.916. The leaf acetone extract had minimum cytotoxicity with the lethal concentration (LC50) of 0.63 mg/mL. Conclusions The results obtained in this study validated the protective effect of C. bispinosa against oral infections.